2011
DOI: 10.1002/hyp.8221
|View full text |Cite
|
Sign up to set email alerts
|

Identification of robust hyperspectral indices on forest leaf water content using PROSPECT simulated dataset and field reflectance measurements

Abstract: Abstract:In this study, we aim at finding efficient and robust hyperspectral indices for estimating forest leaf water content parameters (equivalent water thickness, EWT and fuel moisture content, FMC), which are useful for the understanding of terrestrial ecosystem functioning and evaluating fire risk. The most efficient hyperspectral indices have been identified (both on the context of index types and wavelength domains) using both a simulated dataset generated from the calibrated leaf reflectance model, PRO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 50 publications
0
24
1
3
Order By: Relevance
“…NDVI and CIred edge, which are sensitive to greenness of vegetation rather than water content, were not significantly related with EWT, but they had significant relationships with GWCD, GWCF, and RWC. Although some studies demonstrated significant relationships between GWCD and NDII/NDMI [17,40], NDII/NDMI was not related to any of the measured variables in this study. To explore the vertical differences in the relationships between VIs and water-related properties at leaf level, we analyzed the relationships for each leaf layer from the top to the bottom of the canopy (Table 6).…”
Section: Estimation Of Water-related Properties At Leaf Levelcontrasting
confidence: 87%
“…NDVI and CIred edge, which are sensitive to greenness of vegetation rather than water content, were not significantly related with EWT, but they had significant relationships with GWCD, GWCF, and RWC. Although some studies demonstrated significant relationships between GWCD and NDII/NDMI [17,40], NDII/NDMI was not related to any of the measured variables in this study. To explore the vertical differences in the relationships between VIs and water-related properties at leaf level, we analyzed the relationships for each leaf layer from the top to the bottom of the canopy (Table 6).…”
Section: Estimation Of Water-related Properties At Leaf Levelcontrasting
confidence: 87%
“…Most published indices are expressed as reflectance or a first-order derivative at a given wavelength (R) [30][31][32], wavelength difference (D) [33,34], simple ratio (SR) [2,31,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], normalized difference (ND) [35,36,[50][51][52] or double differences (DDn) [52,53]. Inverse reflectance differences (ID) such as the anthocyanin reflectance index (ARI) or carotenoid reflectance index (CRI) [54,55] proposed as well.…”
Section: Development Of New Indicesmentioning
confidence: 99%
“…Many important advances in hyperspectral assessments of forest properties have been made using hyperspectral physiologic indices, ‘continuum removal’ methods applied over biochemical absorption centers, and SMA (Asner et al. 2011; Wang and Li 2012).…”
Section: Spectral Vegetation Indicesmentioning
confidence: 99%